EL BULLYING Y LAS RELACIONES INTERPERSONALES EN LOS ESTUDIANTES DE NOVENO AÑO PARALELOS A, F, G, DE EDUCACIÓN BÁSICA DE LA UNIDAD EDUCATIVA FISCOMISIONAL “DANIEL ÁLVAREZ BURNEO” Y LA INTERVENCIÓN DEL TRABAJADOR SOCIAL - Calle Quezada, Isabel Viviana (2020)
he present research work entitled BULLYING AND INTERPERSONAL RELATIONSHIPS IN NINETEENTH YEAR STUDENTS PARALLELS A, F, G, OF THE BASIC EDUCATION UNIT "DANIEL ÁLVAREZ BURNEO" AND THE INTERVENTION OF THE SOCIAL WORKER, was based on a study of students from the "Daniel Álvarez Burneo" Fiscal Educational Unit, where reference was made to the ninth parallel years A, F, G, of Basic Education, to the inspector, counselor and teacher tutors of the mentioned parallels, as a non-probabilistic sample for convenience. A quantitative and qualitative research was applied, allowing to give answer to the general objective: to analyze the influence of the Bullying in the Interpersonal Relations; thus also by means of the quantitative research it was possible to identify the index of Bullying in the students and how this one influences in the Interpersonal Relations of the same ones, whereas through the qualitative research it was possible to characterize its Interpersonal Relations, giving answer to the specific objectives raised in the research. In relation to the methodology the scientific method was used, supported of the auxiliary methods like the inductive, deductive, analytical, synthetic, and in turn the techniques as the survey, the interview the observation and focal group, same that were necessary for the compilation of information referring to the problem object of study. The main findings found in the investigation determine that the Bullying influences in a negative way in the students preventing the communication, the practice of values and the mutual respect, likewise it was determined the 40% of index of Bullying in the students appearing to the pair in men and women being caused within the same classroom and having more prevalence the physical bullying, followed of the verbal one, was able to characterize the interpersonal relations like selective, little assertive, and scarcely homogenous. 5 The intervention of the social worker is fundamental in the educational field, since their functions include prevention, detection of any type of violence and acting in the best way possible on the problem. That is why from the social work approach a social action plan was designed for the Educational Community to raise awareness and prevent bullying and in turn improve interpersonal relationships by contributing to the overall development of students.